2018
DOI: 10.1007/s00439-018-1929-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies)

Abstract: NALCN is a conserved cation channel, which conducts a permanent sodium leak current and regulates resting membrane potential and neuronal excitability. It is part of a large ion channel complex, the "NALCN channelosome", consisting of multiple proteins including UNC80 and UNC79. The predominant neuronal expression pattern and its function suggest an important role in neuronal function and disease. So far, biallelic NALCN and UNC80 variants have been described in a small number of individuals leading to infanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Mutations of these genes in C. elegans and Drosophila often cause closely similar phenotypes (Humphrey et al 2007;Jospin et al 2007;Yeh et al 2008;Lear et al 2013;Xie et al 2013;Moose et al 2017), exemplifying the functional interdependency of these proteins. In human, UNC80 and NALCN mutations are the causes of complex syndromic diseases (Köroglu et al 2013;Al-Sayed et al 2013;Perez et al 2016;Stray-Pedersen et al 2016;Fukai et al 2016;Bramswig et al 2018) that are collectively called NALCN channelopathies (Bramswig et al 2018). A notion derived from these studies is that NALCN, UNC80 and UNC79 should be expressed in the same neurons to perform their functions.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of these genes in C. elegans and Drosophila often cause closely similar phenotypes (Humphrey et al 2007;Jospin et al 2007;Yeh et al 2008;Lear et al 2013;Xie et al 2013;Moose et al 2017), exemplifying the functional interdependency of these proteins. In human, UNC80 and NALCN mutations are the causes of complex syndromic diseases (Köroglu et al 2013;Al-Sayed et al 2013;Perez et al 2016;Stray-Pedersen et al 2016;Fukai et al 2016;Bramswig et al 2018) that are collectively called NALCN channelopathies (Bramswig et al 2018). A notion derived from these studies is that NALCN, UNC80 and UNC79 should be expressed in the same neurons to perform their functions.…”
Section: Discussionmentioning
confidence: 99%
“…NALCN channel functions as a multi-protein complex which consists of NALCN, FAM155, UNC-79, UNC80 and other proteins (Cochet-Bissuel et al, 2014). Mutations in the genes of human NALCN or UNC-80 lead to a spectrum of neurological diseases (Bramswig et al, 2018), including infantile hypotonia, psychomotor retardation, and characteristic facies (IHPRF) (Al-Sayed et al, 2013;Koroglu et al, 2013) and congenital contractures of the limbs and face, hypotonia, and developmental delay (CLIFAHDD) (Chong et al, 2015). In addition, a gain-of function mutation of NALCN in mouse causes the dreamless phenotype, suggesting the function of NALCN in rapid eye movement sleep (Funato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 178 bp deletion in NALCN (a gene related with adductive thumbs) disrupted an ADE in the cerebellum and exhibited a sharp difference in enhancer activities between monkeys and apes ( Figure 5F and Table S26). It was reported that NALCN was also associated with neurodevelopmental diseases (Bramswig, et al 2018) and the mutation of NALCN leads to syndromic neurodevelopmental impairment (Fukai, et al 2016). Another example is the ASSV (242 bp deletion) within an ADE in PcGm in TLN2 ( Figure 5A), a brain-function-related gene (Gusareva, et al 2018;Mendez-David, et al 2017).…”
Section: Discussionmentioning
confidence: 99%